Five On A Secret Trail - Blyton, Enid (London Hodder Children's Books, 2015)
The Famous Five are camping near an old ruined cottage - but is the cottage really abandoned? Anne hears strange noises at night, but the others don't believe her! Then they see ghostly lights .
Keywords: Children's Literature - Fiction : Adventure